Culture of interethnic relations in the structure of humanitarian education - Y. V. Levcheniuk (Ukrainian Cultural Studies, 2021)
Goal. To carry out socio-philosophical conceptualization of the phenomenon of culture of interethnic relations as a factor of interaction between representatives of different cultures and nationalities. Today, culture is one of the identifiers in the modern world, which determines the originality and uniqueness of nations and ethnic groups. Theoretical basis. The authors proved that the culture of interethnic relations is a direct dialogue between representatives of different nationalities, which allows the existence and development of national culture in modern society (mass, virtual, global, information) and so on. It is substantiated that the main condition and consequence of the interaction of representatives of different nationalities and ethnic groups is the recognition of their originality and uniqueness, at the same time there is a formation of global identity, i.e. there is an awareness of the need to live together. Scientific novelty. It is substantiated that at the present stage of development, society is in a state of radical large-scale, systemic transformations. Humankind needs to learn the culture of interethnic relations, as modern migration flows change the cultural picture around the world, in particular in the United States and Western Europe. The culture of "aging" Europe is changing significantly under the pressure of migratory flows, which assert their own culture and religion. Conclusions. The beginning of the XXI century characterized by the development of post-globalization, which simultaneously affirms the global and national identity. Humankind recognizes the fact that political and economic factors are secondary to culture and religion, which are the main identifiers of nations and ethnic groups. It is culture that accumulates in itself the necessary, stable set of symbols, which both at the individual and collective level are the defining features of ethnic groups, nations, states. The nation or the state which is able to answer affirmatively the question "who are we?" is successful and strong at the geopolitical level.